2020
DOI: 10.1038/s41598-020-65070-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Convolutional Networks for the Advance Prediction of ENSO

Abstract: el niño-Southern oscillation (enSo), which is one of the main drivers of earth's inter-annual climate variability, often causes a wide range of climate anomalies, and the advance prediction of enSo is always an important and challenging scientific issue. Since a unified and complete ENSO theory has yet to be established, people often use related indicators, such as the Niño 3.4 index and southern oscillation index (SOI), to predict the development trends of ENSO through appropriate numerical simulation models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
106
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(111 citation statements)
references
References 48 publications
(42 reference statements)
5
106
0
Order By: Relevance
“…The experiments showed that the model using TCN produced better forecasting compared to other classic machine learning approaches. As the El Niño-Southern Oscillation (ENSO) prediction accuracy of current popular numerical methods was not high, Yan et al [47] proposed an ensemble empirical mode decomposition and TCN hybrid approach to obtain ENSO prediction results and the correlation coefficient between the worst predicted southern oscillation index and the actual value reached 0.64.…”
Section: Other Potential Deep Learning Methodsmentioning
confidence: 99%
“…The experiments showed that the model using TCN produced better forecasting compared to other classic machine learning approaches. As the El Niño-Southern Oscillation (ENSO) prediction accuracy of current popular numerical methods was not high, Yan et al [47] proposed an ensemble empirical mode decomposition and TCN hybrid approach to obtain ENSO prediction results and the correlation coefficient between the worst predicted southern oscillation index and the actual value reached 0.64.…”
Section: Other Potential Deep Learning Methodsmentioning
confidence: 99%
“…Recent work suggests that ML approaches can predict the Nino3.4 index more skillfully than dynamical forecast systems with lead times of more than a year (Yan et al, 2020, He and Eastman 2020, Ham et al 2019, Dijkstra et al 2019, largely using different types of neural networks, for example, deep neural networks, convolution neural networks (CNN), and recurrent neural networks like the convolution long short-term memory. The lack of sufficient observational data was overcome in one study (Ham et al 2019) by using Earth system model (ESM) simulations: a CNN network was trained with global SST and heat content data from historical simulations of 21 CMIP5 models to predict the Nino3.4 index.…”
Section: Rationalementioning
confidence: 99%
“…However, the energy sector applications of such technology are still barely studied. R. [21]. In this research, a comparative experiment was carried out between LSTM and TCN, where TCN outperforms LSTM using various time-series datasets.…”
Section: Introductionmentioning
confidence: 99%